An Investigation into Adolescents’ Self-perception as Readers - Myo Thandar Cho (Technium Social Sciences Journal, 2020)
The purpose of this study is to investigate adolescents’ (Grade 8, Grade 9, and Grade 10 students) self-perception as readers. The sample consisted of 184 students (91 males and 93 females). Students’ self-perception as readers were measured by using Reader Self-perception Scale 2 was developed by Henk, Melnick, and Marinak (2013). Descriptive statistics, independent sample t test, and one-way ANOVA were used for data analysis. This study showed that young learners’ self-perception as readers was satisfactory. According to the results of the t test, female students’ self-perception as readers was significantly higher than that of male students at p < .05. One-way ANOVA revealed that Grade 10 students’ self-perception as reader specifically in progress category was highest among Grade 8, Grade 9, and Grade 10 students at p < .01.